2016
DOI: 10.14302/issn.2572-5424.jgm-15-815
|View full text |Cite
|
Sign up to set email alerts
|

The role of BCL-2 and BAK genes in chronic kidney disease and haemodialysis patients

Abstract: Background: Polymorphonuclear leucocytes are the first line of defence against foreign invaders and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…The current study investigated whether the circulating Bcl-2 in the CKD cats was significantly lower than those found in clinically normal age-matched cats. In agreement with previous studies, decreased Bcl-2 was also detected in other species with kidney problems ( 8 10 , 27 ). According to Zhang et al ( 8 ), Bcl-2 immunostaining in the kidney tissues of rats with UUO was less detectable than in the control group.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The current study investigated whether the circulating Bcl-2 in the CKD cats was significantly lower than those found in clinically normal age-matched cats. In agreement with previous studies, decreased Bcl-2 was also detected in other species with kidney problems ( 8 10 , 27 ). According to Zhang et al ( 8 ), Bcl-2 immunostaining in the kidney tissues of rats with UUO was less detectable than in the control group.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with a recent mouse study, Bcl-2 mRNA was substantially expressed in the UUO3 group but decreased in the UUO7 and UUO14 groups ( 9 ). Additionally, a prior investigation on human patients found that Bcl-2 levels were lower in patients with end-stage renal disease patients than in individuals with chronic kidney disease ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations